PENGEMBANGAN LKS BERBASIS VIDEO PERCOBAAN GIROSKOP SEBAGAI MEDIA PEMBELAJARAN FISIKA SMA PADA TOPIK PENERAPAN KONSEP HUKUM KEKEKALAN MOMENTUM SUDUT - Hikmah, Dian Hikmah; Sudrajad, Hendar Sudrajad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The purpose of this R&D research is to produced student worksheet based on gyroscope experiment’s video as a physics learning media of senior high school on the topic of application of the law of conservation of angular momentum. This research was conducted at the Laboratory of Physics Education Riau University in December 2014 until June 2015. There were four phases of this research that are preliminary studies, design, develop and validate. We need three lecturers of physics education and two teachers of physics to validate our product. From the results obtained a description that student worksheet based on gyroscope experiment’s video developed has been valid with average scores of 3.56 for the gyroscope experiment’s video and 3.51 for student worksheet based on gyroscope experiment’s video with very high category for all devices. Therefore, student worksheet based on gyroscope experiment’s video declared eligible to be used as a physics learning media of senior high school in the material application of the concept of angular momentum conservation law. Key words: research and development, student worksheet based on gyroscope experiment’s video